2022
DOI: 10.4269/ajtmh.21-1203
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Plasmid-Mediated Colistin Resistance-1-Positive Escherichia coli in Humans, Animals, and Environment on Farms in Vietnam

Abstract: Plasmid-Mediated Colistin Resistance 1 (mcr-1) was first reported in 2015 and is a great concern to human health. In this study, we investigated the prevalence of mcr-1 and mcr-1-positive Escherichia coli (MCRPEC) and the association in infection status among various reservoirs connected to livestock. The study was conducted in 70 poultry and swine farms in a commune in Ha Nam province, northern Vietnam. Samples were collected from farmers, food animals, domestic animals, and farm environments (flies and waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…Notably, the results identified flies as the biggest host of this pathogen with 46.8% of samples infected by OPEfs. This prevalence was higher than the prevalence reported in a study on the carriage of mcr-1-positive Escherichia coli in Vietnam (36.7%) [ 29 ]. Carriage of resistant pathogens in flies was also reported in China [ 47 ].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Notably, the results identified flies as the biggest host of this pathogen with 46.8% of samples infected by OPEfs. This prevalence was higher than the prevalence reported in a study on the carriage of mcr-1-positive Escherichia coli in Vietnam (36.7%) [ 29 ]. Carriage of resistant pathogens in flies was also reported in China [ 47 ].…”
Section: Discussioncontrasting
confidence: 69%
“…In addition, poor living conditions (improper lavatories, untreated wastewater, poor hygiene, etc.) and close interactions between farmers with food animals and the farm environment can facilitate the transmission of resistant bacteria, including Enterococcus , from animals to humans and vice versa [ 28 , 29 , 30 , 31 ]. The emergence of antimicrobial resistance in the livestock industry, especially resistance to critically important antimicrobials such as linezolid [ 32 ], poses a serious threat to public health [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Additionally, bacterial strains harboring mcr-1 have been isolated from clinical specimens, animals, communities, and food in Vietnam. 33,34 Notably, we recently detected mcr-9-carrying IncHI2 plasmids in BSI-causing Enterobacteriaceae at our hospital. 35 Thus, the spread of mobile colistin resistance genes may contribute to the high rate of resistance to colistin.…”
Section: Discussionmentioning
confidence: 91%
“…Recent reports by other groups showed the prevalence of mcr - E . coli to be 14%–38% in human stool samples from Vietnam [ 24 , 25 ] and Bolivia in South America [ 26 ]. Although it is lower than the carriage rate observed in the present study, it is presumed that this may be due to differences in the experimental conditions and participants.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a high carriage rate of approximately 70% of colistin-resistant mcr-E. coli in the residents of all three communities, Santo Domingo and Puyo in Ecuador and Nguyen Xa in Vietnam. Recent reports by other groups showed the prevalence of mcr-E. coli to be 14%-38% in human stool samples from Vietnam [24,25] and Bolivia in South America [26].…”
Section: Prevalence Of Colistin-resistant E Coli Carrying Mcrmentioning
confidence: 99%